Erectile Dysfunction and Low Serum Testosterone in Indian Diabetic Men: Prevalence and Risk factors: ED and testosterone deficiency in diabetic men - Maldar, Aasim; Shingare, Awesh; Chauhan, Phulrenu; Shah, Nishitkumar; Chadha, Manoj (Archives of Men's Health, 2022)
Introduction: Diabetic male patients are more likely to have ED and subnormal testosterone levels than non-diabetic men. We aimed to estimate the prevalence of ED and low serum testosterone level in diabetic men, and to study the patient’s age, duration of diabetes, body mass index (BMI), glycosylated hemoglobin (HbA1c) and spot urine albumin to urine creatinine ratio (uACR) as risk factors for ED, and their correlation with serum total testosterone level. Methods: This was a cross-sectional observational study, including 103 male patients aged 30-60 years, diagnosed with type 2 diabetes mellitus (T2DM). Patients with score less than 22 on the abridged 5-item version of the International Index of Erectile Function (IIEF-5) questionnaire were diagnosed to have ED, and patients with serum total testosterone level less than 2.3ng/ml (8nmol/L) were considered to have low serum testosterone. Results: The prevalence of ED was 46.6%, and that of low testosterone level was 18.4%. Men with ED had significantly higher prevalence of testosterone deficiency than those without ED (31.3% vs 7.3%, P=0.004). Mean age of the patient (50.73±7.22 vs 47.51±8.67 years, P=0.045), mean duration of diabetes (10.66±5.56 vs 8.53±5.60 years, P<0.001), mean BMI (28.51±4.05 vs 24.51±3.32 kg/m2, P<0.001), and mean HbA1c (8.49±1.15 vs 7.70±1.05 %, P<0.001) were higher, while mean total testosterone level (3.18±1.65 vs 4.61±1.92 ng/ml, P<0.001) was lower in patients with ED, compared with those without ED. Total testosterone level negatively correlated with BMI (R=-0.682, P<0.001), HbA1c (R=-0.279, P=0.004), and uACR (R=-0.241, P=0.014); and positively correlated with IIEF-5 questionnaire score (R=0.519, P<0.001). BMI (P<0.001) and uACR (P=0.048) independently and negatively correlated with total testosterone level. Conclusion: ED is a common complication in Indian men with T2DM. Excess weight is a risk factor for ED as well as low testosterone level. Older age, longer duration of DM and poor glycemic control are risk factors for ED, and presence of microalbuminuria is associated with low testosterone level. Serum testosterone levels should be measured in diabetic men suffering from ED.